PENERAPAN PERMAINAN TRADISIONAL DALAM MENINGKATKAN MINAT BELAJAR PJOK SISWA KELAS 3 DI SDN 12 KOTO BARU - Tuti Hariani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
From the research results, the researcher raised the topic of implementing traditional games in increasing interest in learning physical education, sports and health at SDN 12 Koto Baru. This study uses a qualitative research type with observation and interview methods for teachers and students in grade 3 at one of the state elementary schools 12 Koto Baru, Tiumang District. From the interview questionnaire for teachers and 14 students, it shows a lack of student interest in learning PJOK lessons.